Pelatihan Pembuatan Lampu Jalan Otomatis Dengan Pemanfaatan Tenaga Surya Pada Karang Taruna Di Desa Mojodanu Ngusikan Jombang - Nasirudin, Mohamad; Hartanti, Dyah Ayu Sri; Puspaningrum, Yessita; Zulfikar, Zulfikar; Anwar, Achmad Sholichul; Sudarminto, Ahmad; Rohman, Achmad Ali Fathur; Ramadhan, Galuh; Nuriyah, Selvia Azka; Ashar, Salim (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
In many remote and rural areas, limited access to the main electricity grid often results in lighting issues that impact safety, education, and productivity. To address this problem, the implementation of solar panel technology as an alternative energy source offers a sustainable and effective solution. This community service program aims to introduce and apply solar-powered automatic street lighting technology in Mojodanu Village. The method used is Participatory Action Research (PAR), involving local youth from the Karang Taruna community in training and implementation of this technology. The training conducted in August 2024 included explanations on the operation and functioning of automatic street lights, as well as hands-on practice in assembling these lights. The training results showed an improvement in participants' understanding, with Post-Test scores higher than Pre-Test scores. The benefits of implementing this technology include energy and operational cost savings, as well as providing efficient lighting in areas without access to electricity. Additionally, the project imparts new knowledge and skills to local youth regarding environmentally friendly technology. The outputs of this activity include an understanding of the assembly of automatic street lights, materials and tools used, and practical skills in assembling simple solar panel-based devices.